Efficiency of Amorphous Calcium Phosphate–Containing Orthodontic Composite and Resin Modified Glass Ionomer on Demineralization Evaluated By a New Laser Fluorescence Device - Uysal, Tancan; Amasyali, Mihri; Koyuturk, Alp Erdin; Sagdic, Deniz (European Journal of Dentistry, 2009)
Objectives: The aim of this in vitro study was to compare the efficacy of Amorphous Calcium Phosphate (ACP)-containing orthodontic composite and resin-modified glass ionomer cement (RMGIC) on enamel demineralization adjacent to orthodontic brackets evaluated by a new laser fluorescence device.Methods: Sixty extracted maxillary premolars were used in the present study. Twenty orthodontic brackets were bonded with ACP-containing orthodontic adhesive (Aegis-Ortho), 20 were bonded with RMGIC (Fuji Ortho LC) ad20 were bonded with Transbond XT composite as the control. All samples were then cycled for 21 days through a daily procedure of demineralization for 6 hours and remineralization for 17 hours. After this procedure, demineralization evaluations were undertaken by a pen-type laser fluorescence device (DIAGNO-dent Pen). Analysis ofvariance (ANOVA) and Tukey test was used for statistical evaluation, at P<.05 level.Results: According to ANOVA, significant demineralization variations (ΔD) were determined among groups (F=6.650; P<.01). The ACP-containing composite showed the lowest (mean: 8.98±2.38) and the control composite showed the highest (mean:12.15±3.83) ΔD, during 21 days demineralization process (P<.01). Significant difference was also observed between the ΔD scores of the RMGIC (mean: 9.24±2.73) and control (P<.05).No significant differences was found in preventive effects of ACP-containing composite and RMGIC (P<.05) against demineralization.Conclusions: The use of both ACP-containing orthodontic composite and RMGIC should be recommended for any at-risk orthodontic patient to provide preventive actions and potentially remineralize subclinical enamel demineralization. (Eur J Dent 2009;3:127-134)
Keywords: Demineralization; Amorphous calcium phosphate; Glass ionomer cements